Hemodynamic Behavior of Coronary Stents in Straight and Curved Arteries - Hsiao, Hao-Ming; Lin, Chien-Han; Liao, Ying-Chih; Chen, Hsien-Yeh; Wang, Tzu-Wei (Current Nanoscience, 2014)
Stents are miniature medical devices that can be inserted into arteries and expanded during angioplasty to restore blood flow and prevent arterial collapse. They have been the primary treatment for cardiovascular diseases since the 1990s. However, after stenting, potential risks associated with restenosis may occur, and several studies have shown that stent design could be one of the critical factors in this process. Computational modeling has been widely used as an important tool to predict the clinical performance of stents and hemodynamic behavior in stented arteries. In this study, computational fluid dynamics models were developed to investigate the effects of cardiovascular stent design on the wall shear stress distribution in straight and curved coronary arteries. Results showed that the stent design pattern alone did not have a significant impact on stent hemodynamics; however, stenting in curved arteries increased the low shear stress area, the region where wall shear stress is less than 5 dynes/cm2, which may lead to a higher restenosis rate. The total surface area of low wall shear stress almost doubled when the angle of artery curvature increased from 0o to 90o. The implication is that stent implantation in a tortuous artery greatly increases the risk of restenosis. The proposed methodology and findings show that the presence of a stent in straight or curved arteries alters the flow field and wall shear stress distribution within arteries, providing great insight for the future design optimization and physician practice to help achieve the best possible clinical outcomes.
Keywords: Hemodynamics